Peran Zakat, Pdrb (Produk Domestic Bruto), PMA (Penanaman Modal Asing), PMDN (Penanaman Modal Dalam Negeri) Terhadap Pengentasan Kemiskinan di Kabupaten Tapanuli Tengah - Khairul Akhyar; Nurul Jannah (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
Poverty is a multidimensional problem that remains a major development challenge in Central Tapanuli Regency. Growth in Gross Regional Domestic Product (GRDP), increased realization of Foreign Direct Investment (PMA) and Domestic Direct Investment (PMDN), and zakat collection should be important instruments in reducing poverty rates. However, data from 2019–2023 shows a discrepancy, where the growth in these macroeconomic and social indicators is not accompanied by a decrease in the number of poor people. This study aims to analyze the influence of zakat, GRDP, PMA, and PMDN on poverty levels in Central Tapanuli Regency. The research method used is qualitative descriptive analysis with secondary data from BPS, BAZNAS, and BKPM as well as interviews with relevant parties. The results show that zakat does contribute to alleviating the burden on mustahik, but its role is still limited because the majority of distribution is consumptive. GRDP increased from Rp9.95 trillion in 2019 to Rp13.67 trillion in 2023, but the resulting economic growth is not yet inclusive. Foreign direct investment (FDI) tends to be oriented towards large capital with limited labor absorption, while domestic direct investment (PMDN) is closer to local needs but still less than optimal in poverty alleviation. Overall, the increase in zakat, GRDP, FDI, and PMDN has not been able to reduce the poverty rate, which actually increased from 376,474 people in 2019 to 489,760 people in 2023. Thus, a more inclusive development strategy, optimization of productive zakat, and investment policies that favor labor-intensive sectors and MSMEs are needed so that economic growth truly impacts poverty reduction.